IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU SEKOLAH DASAR DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2012 - Elmi Rahmayanti; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Education has important implication to build civilizations. with education everyone could develop potential in themselves and survive in life. Teacher certification as an effort to boost teacher’s qualification is also expected to improve learning quality and quality education continuously. This research to explain implementation teacher’s certification in elementary school to improve the quality of education. This research using theory of implementing public policy from Daniel A. Mazmanian and Paul A. Sabatier with qualitative approach ang descriptive method. This research is done trough with indepth interview and documentation technique. Data analysis with reduiction, organization and interpretation data.The result of this research is the implementation of teacher’s certification is working unwell, they have not increase in performance significantly. This problem is effect from there are not rule about implementation of teacher’s certification after get the professional educator certificate. Less of comitmen and skills of the teacher and low concern who society have about education development in Kecamatan Keritang.Keyword : Implementating public policy, teacher’s certification